2020
DOI: 10.1177/1075547020953603
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Origins of COVID-19

Abstract: Conspiracy theories have flourished about the origins of a novel coronavirus (SARS-CoV-2) that causes an acute respiratory syndrome (coronavirus disease 2019 [COVID-19]) in humans. This article reports the results from a study that evaluates the impact of exposure to framed messages about the origins of COVID-19. We tested four hypotheses: two focusing on its origins as either zoonotic or human-engineered and two concerning the impacts of origin beliefs on the desire to penalize China or support increased fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 82 publications
4
52
0
2
Order By: Relevance
“…8 Some are optimistic that the ongoing nature of the threat of climate change will lead to increasing links of climate and COVID-19 in the media over time, 7 yet time will tell. This Comment can support ongoing examinations of the content and framing of COVID-19 stories, 5 and support considerations of the capacity to respond to science policy collective action problems. 9,10 Further research is needed to explore factors that can best explain these trends and how media coverage can effectively connect the dots between intersecting and significant crises in 2020 and beyond.…”
Section: Covid-19 Media Coverage Decreasing Despite Deepening Crisismentioning
confidence: 80%
See 1 more Smart Citation
“…8 Some are optimistic that the ongoing nature of the threat of climate change will lead to increasing links of climate and COVID-19 in the media over time, 7 yet time will tell. This Comment can support ongoing examinations of the content and framing of COVID-19 stories, 5 and support considerations of the capacity to respond to science policy collective action problems. 9,10 Further research is needed to explore factors that can best explain these trends and how media coverage can effectively connect the dots between intersecting and significant crises in 2020 and beyond.…”
Section: Covid-19 Media Coverage Decreasing Despite Deepening Crisismentioning
confidence: 80%
“…3 Media stories about the pandemic have been found to have substantial effects on peoples' beliefs about its origins, opinions about appropriate policy responses, and overall politicisation of the crisis. 4,5 We found that the proportion of media coverage that mentioned COVID-19 (with terms such as COVID or coronavirus) in early 2020 increased dramatically within 102 high-circulation newspaper sources across 50 countries around the world. This topic emerged as a dominant media storyline just as media coverage of climate change dropped precipitously over the same period across the same sources.…”
Section: Covid-19 Media Coverage Decreasing Despite Deepening Crisismentioning
confidence: 88%
“…More specifically, people who believe in the unnatural origin of COVID-19, report less support for biomedical research of zoonotic viruses 74 . Interestingly, belief in the artificial creation theory is negatively correlated with self-reported knowledge about COVID-19 15 .…”
Section: Beliefs Biases and Attitudesmentioning
confidence: 99%
“…In the Gompertz curve, T max (θ) represents the inflection value after a period of rapid growth. Finally, we will also estimate the Gompertz curve given by Expression (2).…”
Section: The Characteristics Of Interest and How To Estimate Themmentioning
confidence: 99%
“…In December 2019, the number of pneumonia cases inexplicably increased in China. Later, scientists discovered that they were caused by a novel kind of coronavirus, called SARS-CoV-2, which appeared for the first time in Wuhan, China, see [1,2]. From that date, the disease began spreading in a huge number of countries and regions outside China where have confirmed new cases and deaths almost every day.…”
Section: Introductionmentioning
confidence: 99%